Clarification of Einfeldia Kieffer, 1922 (Diptera: Chironomidae) with E. australiensis (Freeman, 1961), comb. n. based on immature stages - Cranston, Peter S.; Martin, Jon; Mulder, Monica; Spies, Martin (Zootaxa, 2016)
The immature stages are described for the first time for Chironomus (Xenochironomus) australiensis Freeman (Diptera: Chironomidae) and the adult male is redescribed including from type specimens. The species does not belong to Chironomus Meigen or Xenochironomus Kieffer, but is best placed in a modestly expanded Einfeldia Kieffer. Application of this genus name is clarified, including by a lectotype fixation for its type species, E. pectoralis Kieffer, 1924. Einfeldia australiensis (Freeman) comb. n. provides the first record of the genus from Australia; otherwise the genus is reported confidently only from North America, Central America and western Europe to Japan. The immature stages of E. australiensis occur in relatively shallow mesotrophic to eutrophic dune lakes and maars with circum-neutral pH and high conductivity, from southeastern Queensland to southern Australia. The cytology is described briefly from larval salivary glands. Alternative genus placements for the species are discussed, and problems with Einfeldia and connected systematics in the tribe Chironomini are addressed.